Social Media and the Political Empowering of the Iranian People - Omidi, Ali; MORADIFAR, Saeedeh (Cyberpolitik Journal, 2022)
Technologies such as smartphones and social media offer their users the opportunity to present and exchange their ideas and information as active social players. Meanwhile, Iran is one of the leading countries in which the penetration rate of social media is massive. The power of sharing information, participation, promotion, and political mobilization of social media in Iran can be seen in many fields. This research seeks to answer the question of how social media have had an impact on political empowerment by enlarging people's freedoms and opportunities and improving their influence. The research findings suggest that social media has become the platform for protesting the state policies through sharing and disseminating information, making new narratives, campaigning, and field actions due to restrictions to conventional media; so the unilateral impact of the state media’s discourse has been diminishing drastically. It challenges the state policies and clichés; and the Iranian state has been forced to hear the voices of the people partially as well as to increase its accountability. This research is probing its hypothesis by analyzing four major events in Iran in which social media played an impressive role in 2017-2018. This research based on mainly to internal sources from inside Iran.